2023
DOI: 10.1039/d3gc00712j
|View full text |Cite
|
Sign up to set email alerts
|

Visible light-initiated manganese-catalyzed hydrosulfonylation of alkenes

Abstract: Strategies for the preparation of sulfones have received much attention because they have found widespread applications in the areas of pharmaceutical, agrochemical, and material sciences. Although the radical hydrosulfonylations of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Based on our mechanistic studies as well as previous disclosures, 19–21 we proposed a possible reaction mechanism, which is depicted in Scheme 5. Under irradiation by white light, L1 Mn(CO) 3 ˙ ( I ) is generated from the homolysis of L1 2 Mn 2 (CO) 6 , which is formed in situ from Mn 2 (CO) 10 and the ligand ( L1 ) (see ESI Fig.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Based on our mechanistic studies as well as previous disclosures, 19–21 we proposed a possible reaction mechanism, which is depicted in Scheme 5. Under irradiation by white light, L1 Mn(CO) 3 ˙ ( I ) is generated from the homolysis of L1 2 Mn 2 (CO) 6 , which is formed in situ from Mn 2 (CO) 10 and the ligand ( L1 ) (see ESI Fig.…”
Section: Resultsmentioning
confidence: 74%
“…Based on our mechanistic studies as well as previous disclosures, [19][20][21] we proposed a possible reaction mechanism, which is depicted in Scheme 5. Under irradiation by white light, L1Mn(CO) 3…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Taking advantage of the green and efficient photochemical strategies, significant progress is being achieved in the synthesis of alkyl-substituted sulfones. Sulfonyl chlorides, 9–13 sulfinate salts, 14–17 sulfonamides, 18,19 tetrazole sulfones 20 and a mixture of DABCO·(SO 2 ) 2 and alkyl Hantzsch ester 21 have been employed as sulfonyl radical precursors in the anti-Markovnikov addition reaction to feedstock alkenes (Scheme 2). The Gouverneur group reported the elegant use of commercially available sulfonyl chlorides for photoredox-catalyzed hydrosulfonylation; however, external hydrogen atom donors such as tris(trimethylsilyl)silane are essential.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a radical clock experiment with (1-cyclopropylvinyl)benzene 6a under the standard conditions exclusively furnished the ring-opened product 7a in 79% yield and the coupling product 8a in 82% yield, which demonstrated the intermediacy of the sulfonyl radical and demonstrated that 4-(trifluoromethyl)benzenethiol was the source of hydrogen in this transformation (Scheme 2b). 15 Lastly, deuterium labeling experiments were performed (Scheme 2c): (1) use of D 2 O under the standard conditions afforded the mixed H/D product in 84% yield (27% of D); and (2) including D 2 O without 4-(trifluoromethyl)benzenethiol in the reaction did not work. In addition, when only 4a was reacted in D 2 O, no deuterated product was detected.…”
mentioning
confidence: 99%